PESANTREN SEBAGAI DESTINASI WISATA:: Studi Awal atas Pondok Pesantren “Aliran Sesat” Biharu Bahri ‘Asali Fadlail al-Rahmah Malang Jatim - Siti A'isyah (LP3M IAI Al-Qolam, 2020)
This research focuses on Islamic boarding school (pondok pesantren) as religious tourism destination. Religious tourism is an important part of the international tourist market, including in Indonesia. Indonesian government has realized the role of this kind of tourism in economic development. Hence, every intake has been being taken to develop it, including promoting new destinations. One of them is pondok pesantren (Islamic boarding school) because it’s a unique subculture. Pondok Pesantren Biharu Bahri ‘Asali Fadlail al-Rahmah, which is located in Malang East Java, is one of them. It has luxurious, artistic as well as unique building. It’s also accused as deviationist. The main questions are the motivation of constructing the building, the process of the construction, and the effects of becoming the destination of tourism on the existence of Pondok Pesantren Biharu Bahri ‘Asali Fadlail al-Rahmah. The main motivation of the construction was ‘da’wah’ through building instead of words. The construction didn’t use any architect or other expert and financially self supported. The only inpsiration is ‘ilham’ (divine inspiration) of Kiai. Even the workers are the students themselves. Meanwhile, becoming tourism destination affected this pondok pesantren both positive and negative effects. Positive effects includes the mission of da’wah and economic empowerment, while the negative ones are inappropriate tourist activities, overcrowding as well as commercialization.